Clinical Outcome Controversy in Helicobacter pylori Infection - Muhammad Miftahussurur; Heasty Oktaricha; Titong Sugihartono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
H. pylori infection can manifest as intestinal and extraintestinal disease. In this review, we summarize several factors that cause differences in clinical manifestations of H. pylori infection. Host inflammatory response and bacterial virulence are key in determining the pattern of acid secretion and gastritis. The acid level factor that has a greater effect, not H. pylori infection itself. Gastritis predominant in the gastric in the initial phase will produce higher acid and trigger GERD. H. pylori is also the cause of gastric adenocarcinoma. Different vacA genotypes are related to the risk of clinical manifestations such as peptic ulcer or gastric cancer. However, there is variance prevalence in some countries which can be explained through a combination of several factors including age at infection, virulence factors of H. pylori, host genetic profile, and environmental factors. Besides, important differences were found at a locus in CagA H. pylori which resulted in differences in clinical outcomes in the form of gastritis or MALT lymphoma. H. pylori infection alone is not enough to trigger  idiopathic thrombocytopenic purpura (ITP). Additional triggers are needed to obtain an anti-platelet autoimmune response at ITP associated with H. pylori. Therefore, the difference in clinical manifestations of H. pylori infection remains controversial. H. pylori is not only a single cause, but the host and environmental factors also contribute to producing different responses.